Forestry meets Steel. A system study of the possibility to produce DRI (directly Reduced Iron) using gasified biomass. - Grip, Carl-Erik; Toffolo, Andrea; Östman, Marianne; Sandberg, Erik; Orre, Joel (Luleå tekniska universitet, Energivetenskap, 2015)
The main production of primary Iron from ore is now made by reduction using fossil reductants, either by producing hot metal in the blast furnace process or as directly reduced iron with natural gas as most common reductant. The climate gas impact would be improved if at least part of the reductants could be produced from Biomass. One possibility could be to use gasified Biomass to produce DRI (Directly Reduced Iron). This is studied in a cooperative project where LTU, MEFOS, ETC and five industries in the areas forestry & pulp, mining, iron and gas are involved. The investigation is made in four parts where the first one is on the supply of biomass. A large amount of Biomass has to be delivered into a single site to exchange a large amount of fossil reductant. Also, forestry by-products should be used as most of the round wood is reserved for other uses. Harvesting, logistics and economics are considered. The second part is on the gasification of the biomass, where the aim is to use to produce hot gas that can be used directly. Pilot experiments are carried out using oxygen in an entrained flow gasifier. The third part is on the metallurgical processes, where reduction tests are carried out with gas that can be produced in the gasifier. The limitations of the gas content are studied as well as the effect on DRI. Also the suitability of the DRI product is evaluated. The fourth part of the project uses process integration to model the whole process chain. The results from the other project parts are used to build the system model. It is then used for technical economic optimization the whole system harvesting-transport-gasifier-direct reduction-use of DRI. The first use of the system model has been to find the best supply road (harvesting, pretreatment and transport) for a chosen production case The simulations indicated that the supply of residuals is possible but will need material from a large part of the north Sweden wood area, and that a relatively large amount of gas recirculation is needed. The ...